First report of Neopestalotiopsis clavispora and N. protearum causing leaf spot in Annona muricata (soursop) - Yabar, Gabriela Cecilia; Wong, Julio Alfonso Chia; Pereira, Jadergudson (Phytotaxa, 2025)
Fungal pathogens are increasingly recognized as major threats to global agriculture, with emerging species posing new challenges to crop health and productivity. This study reports, for the first time in Peru and in Annona muricata (soursop), the identification of Neopestalotiopsis clavispora and N. protearum as causal agents of leaf spot and fruit rot. Pathogenicity assays confirmed that both species infect foliar and fruit tissues in both commercially important cultivars (“common” and “Giant Criolla”), demonstrating their disease-causing potential under controlled conditions. Morphological characterization and multi-locus phylogenetic analyses (ITS, β-tubulin, and TEF1-α) confirmed the identity and taxonomic placement of both species within the Neopestalotiopsis clade. The findings represent a significant expansion of the known host range and geographic distribution of these fungi, which are already documented on a wide range of tropical and subtropical crops. Given their broad host plasticity and ecological adaptability, Neopestalotiopsis spp. may pose an increasing risk to diverse agricultural systems, especially under shifting environmental conditions. This study highlights the importance of developing species-specific diagnostic tools, implementing proactive surveillance, evaluating host resistance, and advancing research into epidemiology and control strategies to mitigate the risk of future outbreaks.